2021
DOI: 10.3126/kumj.v19i4.49784
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Scrub Typhus in Patients Attending Dhulikhel Hospital, Kavre

Abstract: Background Scrub typhus is a largely ignored tropical disease and a leading cause of undifferentiated febrile illness. It is caused by Orientia tsutsugamushi. Scrub Typhus is frequently observed in South Asian countries. However, clear epidemiological information of this disease is lacking in case of Nepal. Nepal has shown steady increase in cases of Scrub Typhus since 2015. The epidemiological data related to this disease would support the decision making and surveillance design for early outbreak detection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Specifically, the samples were collected between July and November, which coincides with the rainy monsoon and post-monsoon seasons and the peak growth of vegetation and mite populations. Notably, the majority of studies included in our review consistently reported higher seroprevalence (over 90% of total cases) during the period of July–November 14 , 16 , 17 , 19 , 20 , 24 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Specifically, the samples were collected between July and November, which coincides with the rainy monsoon and post-monsoon seasons and the peak growth of vegetation and mite populations. Notably, the majority of studies included in our review consistently reported higher seroprevalence (over 90% of total cases) during the period of July–November 14 , 16 , 17 , 19 , 20 , 24 .…”
Section: Discussionmentioning
confidence: 60%
“…Females were found to be more affected than males in this review. This could be attributed to the higher exposure of women to mites while working in scrub-prone areas, such as agricultural fields during harvesting or cultivation of crops, or in forests 16 , 17 , 19 , 48 . Conversely, most men were less exposed to mites as they were predominantly engaged in indoor work, such as office jobs, factory work, or employment in companies 16 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to a study done in Dhulikhel Hospital, Nepal. 7 Severe scrub typhus showed involvement in one or the other systems like acute hepatitis, sepsis, cardiac failure, ARDS, encephalitis, DIC and death. These complications were encountered in 7 (18.42%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Dhulikhel Hospital earlier and Kathmandu valley reported similar prevalence of the Scrub typhus. 16,17 However, the studies had some differences in duration, sample size and the types of departments the patient were examined. Also, the changes in the living standard and the lifestyle might have contributed to the increasing number of cases in Nepal.…”
Section: Discussionmentioning
confidence: 99%